A systematic review of the factors associated with interest in predictive genetic testing for obesity, type II diabetes and heart disease. Issue 5 (14th November 2013) - Collins, J.; Ryan, L.; Truby, H.
Abstract Background In the future, it may be possible for individuals to take a genetic test to determine their genetic predisposition towards developing lifestyle‐related chronic diseases. A systematic review of the literature was undertaken to identify the factors associated with an interest in having predictive genetic testing for obesity, type II diabetes and heart disease amongst unaffected adults. Methods Ovid Medline, PsycINFO and EMBASE online databases were searched using predefined search terms. Publications meeting the inclusion criteria (English language, free‐living adult population not selected as a result of their disease diagnosis, reporting interest as an outcome, not related to a single gene inherited disease) were assessed for quality and content. Narrative synthesis of the results was undertaken. Results From the 2329 publications retrieved, eight studies met the inclusion criteria and were included in the review. Overall, the evidence base was small but of positive quality. Interest was associated with personal attitudes towards disease risk and the provision of information about genetic testing, shaped by perceived risk of disease and expected outcomes of testing. The role of demographic factors was investigated with largely inconclusive findings. Conclusions Interest in predictive genetic testing for obesity, type II diabetes or heart disease was greatest amongst those who perceived the risk of disease to be high and/or the outcomes of testing to be beneficial.